1992
DOI: 10.1055/s-0038-1648412
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Procoagulant Imbalance in Patients with Inherited Thrombophilic Syndromes

Abstract: SummaryIn 107 asymptomatic and untreated patients with inherited syndromes associated with thrombophilia (antithrombin III, protein C and protein S deficiencies), we compared in parallel two plasma peptides which reflect activation of the common coagulation pathway: the prothrombin fragment 1 + 2 (F1+2) and fibrinopeptide A (FPA). Both F1+2 and FPA were measured with simple, commercially available ELISA methods. High levels of F1+2 or FPA were found in about one fourth of the patients as a whole. When patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
2

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 9 publications
4
47
2
Order By: Relevance
“…The patients studied had none of the known congenital or acquired thrombophilic states, in which the circulating levels of markers of activation of the coagulation system may be increased. [21][22][23][24] Even though the recently described G20210A mutation of the prothrombin gene 17 could be looked for retrospectively in only approximately one third of the patients, also those patients in whom the prothrombin mutation was ruled out had high APC levels, excluding that they were mainly due to the presence of the mutation. APC is generated from its plasma precursor, protein C, on activation by thrombin-thrombomodulin complex on the endothelial cell surface, probably acting in concert with the endothelial cell protein C receptor.…”
Section: Discussionmentioning
confidence: 99%
“…The patients studied had none of the known congenital or acquired thrombophilic states, in which the circulating levels of markers of activation of the coagulation system may be increased. [21][22][23][24] Even though the recently described G20210A mutation of the prothrombin gene 17 could be looked for retrospectively in only approximately one third of the patients, also those patients in whom the prothrombin mutation was ruled out had high APC levels, excluding that they were mainly due to the presence of the mutation. APC is generated from its plasma precursor, protein C, on activation by thrombin-thrombomodulin complex on the endothelial cell surface, probably acting in concert with the endothelial cell protein C receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced generation of thrombin measured as increased levels of prothrombin fragment 1+2 (F1+2) or thrombin-antithrombin complexes in basal conditions has been observed in subjects with deficiencies of protein C [14,15] and protein S [14,16] as well as in subjects heterozygous for Gln506-FV [16][17][18][19]. The enhanced thrombin formation has been interpreted to indicate a clinical hypercoagulable state.…”
Section: Introductionmentioning
confidence: 99%
“…However, around twenty years ago they were tested in various small studies that gave contradictory results. Increased F1+2 was found in individuals with antithrombin, protein C and S deficiencies (Demers et al, 1992;Mannucci et al, 1992), as well as in those with activated protein C (APC) www.intechopen.com resistance (Simioni et al, 1996;Bauer et al, 2000), prothrombin G20210A mutation (Bauer et al, 2000) antiphospholipid syndrome (Ames et al, 1996), hyperhomocysteinemia (Kyrle et al, 1997a) and increased levels of factor VIII (O'Donnell et al, 2001). Not all studies, however, confirmed the association of increased F1+2 levels with TF (Kyrle et al, 1998;Eichinger et al, 1999;Lowe et al, 1999).…”
Section: Specific Markers Of Haemostasis Activationmentioning
confidence: 99%